Leveraging LinkedIn: How Can Educators Help College Students Market Themselves?. Issue 6 (3rd June 2022) - Daniels, Ruby A.; Dempsey, Mark
ABSTRACT: To successfully transition from college to career, community college students must be prepared to sell their skills to potential employers. LinkedIn, the world's leading professional networking website, provides college students and graduates with an affordable platform to promote their knowledge, skills, and abilities. Unfortunately, students often do not know how to communicate a unique value proposition in their LinkedIn profiles. In response, the National Convergence Technology Center (CTC), based in Collin College, developed a 30-minute webinar to train community college educators about how to avoid common mistakes in LinkedIn. High interest in the webinar as well as responses to a survey about the session indicate community college educators want to learn how to leverage LinkedIn to help their students find jobs after graduation.